2009
DOI: 10.1021/bi9007287
|View full text |Cite
|
Sign up to set email alerts
|

Isoform-Specific Inhibition of Cyclophilins

Abstract: Cyclophilins belong to the enzyme class of peptidyl prolyl cis/trans isomerases which catalyze the cis/trans isomerization of prolyl bonds in peptides and proteins in different folding states. Cyclophilins have been shown to be involved in a multitude of cellular functions like cell growth, proliferation, and motility. Among the 20 human cyclophilin isoenzymes, the two most abundant members of the cyclophilin family CypA and CypB exhibit specific cellular functions in several inflammatory diseases, cancer deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 69 publications
(139 reference statements)
4
81
0
4
Order By: Relevance
“…Our FEP/MC simulations have indicated that 2 takes advantage of these subtle differences via different binding motifs that fine-tune their selectivity for CypA by exclusively weakening their nonbonded interactions with the catalytic Arg63 and Asn110 residues in CypB. Relative free energies of binding, ΔΔG bind , given in Table 2 for the 2a-2c inhibitors were computed in both CypA and CypB using the MC/FEP transformation sequence given in Figure 9 and were found to yield excellent agreement with the experimental free-energy differences derived from the K i protease-free PPIase assay at pH 7.8 and 283K [113,189]. Figure 10 shows two binding modes for 2a in the overlaid CypA and CypB active sites where the lighter colored structure is the preferred binding conformation in CypA and the darker structure is favored in CypB.…”
Section: Selectivity Towards Cypamentioning
confidence: 71%
See 4 more Smart Citations
“…Our FEP/MC simulations have indicated that 2 takes advantage of these subtle differences via different binding motifs that fine-tune their selectivity for CypA by exclusively weakening their nonbonded interactions with the catalytic Arg63 and Asn110 residues in CypB. Relative free energies of binding, ΔΔG bind , given in Table 2 for the 2a-2c inhibitors were computed in both CypA and CypB using the MC/FEP transformation sequence given in Figure 9 and were found to yield excellent agreement with the experimental free-energy differences derived from the K i protease-free PPIase assay at pH 7.8 and 283K [113,189]. Figure 10 shows two binding modes for 2a in the overlaid CypA and CypB active sites where the lighter colored structure is the preferred binding conformation in CypA and the darker structure is favored in CypB.…”
Section: Selectivity Towards Cypamentioning
confidence: 71%
“…This isomerization has been identified as the rate-limiting step in protein folding [106,107]. Review of the biochemistry of the PPIases is well-represented in the literature with an emphasis on overall biological relevance [108,109], foundational biochemistry [110,111], mechanism [112], inhibitors [113][114][115][116], and possible therapeutic utility [117]. Eight human Cyps with molecular masses ranging from 18 to 150 kDa [107] and an additional 12 multidomain Cyps (masses up to 352 kDa) have been reported that contain a highly conserved active site, making specific inhibition of a particular family member difficult [118].…”
Section: Cyclophilinsmentioning
confidence: 99%
See 3 more Smart Citations